2018
DOI: 10.1080/2162402x.2018.1494488
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages in radiation injury: a new therapeutic target

Abstract: Radiotherapy can induce toxicity in healthy tissues such as radiation-induced fibrosis (RIF), and macrophages are proposed as new profibrogenic cells. In this Point-of-View, we summarize the role of the immune response in ionizing radiation injury, and we focus on macrophages as a new therapeutic target in RIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 28 publications
0
46
0
Order By: Relevance
“…This includes the bystander effect (when the signals from irradiated cells affect neighboring non-irradiated tissue responses) [51,61,85,86,87]. An example is the direct IR effect on the activation of macrophages, which then produce bystander signals and play an important role in the development of radiation injury [88]. An abscopal effect, defined as “an action at a distance from the irradiated volume but within the same organism” is also observed [70,85,89,90,91,92,93].…”
Section: Tumor Milieu As a Critical Immune Mediator Of Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the bystander effect (when the signals from irradiated cells affect neighboring non-irradiated tissue responses) [51,61,85,86,87]. An example is the direct IR effect on the activation of macrophages, which then produce bystander signals and play an important role in the development of radiation injury [88]. An abscopal effect, defined as “an action at a distance from the irradiated volume but within the same organism” is also observed [70,85,89,90,91,92,93].…”
Section: Tumor Milieu As a Critical Immune Mediator Of Rtmentioning
confidence: 99%
“…CAFs are metabolically active, secrete SASP (senescence-associated secretory phenotype) factors (growth factors, proteases, inflammatory mediators, or extracellular matrix proteins) and regulate tumor growth [127,131]. In addition, high doses of IR (>8 Gy) may promote the anti-inflammatory activation of macrophages [88], and a dose of 20 Gy activates the M2 phenotype of TAM with tolerogenic properties by induction of immune inhibitory molecules COX-2/PGE2 and NO [127,132].…”
Section: Different Responses Of the Tme After Various Doses Of Rtmentioning
confidence: 99%
“…rt enhances the antitumor effect of Duox1 −/− proinflammatory macrophages Macrophages are key players in the responses of tumors to radiotherapy and exert either antitumor or protumor effects according to their phenotype. 15 Subsets of macrophages with an immunosuppressive/anti-inflammatory phenotype can limit the efficacy of RT. 16 17 We demonstrated that DUOX1 reduced the proinflammatory properties of macrophages in vitro (figure 1), and we therefore hypothesized that DUOX1 could be involved in macrophage-mediated mechanisms of resistance to RT.…”
Section: Duox1 Decreases the Antitumor Effect Of Proinflammatory Macrmentioning
confidence: 99%
“…Melatonin can attenuate the activity of macrophages [29]. As macrophage activity plays a key role in the release of pro-fibrotic cytokines such as TGF-β, IL-4, IL-10, and IL-13, melatonin may have a beneficial effect in the prevention of the late effects of ionizing radiation through modulation and maintenance of macrophages [30]. Apoptosis and senescence are important types of cell death following exposure to radiation that may be involved in the infiltration of macrophages to irradiated tissues [31].…”
Section: Discussionmentioning
confidence: 99%